Manajemen Bantuan Operasional Penyelenggaraan (BOP) Dalam Meningkatkan Mutu Pendidikan - Rina Kurnia Utami; Yovitha Juliejantiningsih; Rasiman (Universitas Muhammadiyah Bangka Belitung, 2025)
This study aims to analyze the management of Operational Assistance for Implementation (BOP) in improving the quality of education at TK Negeri Pembina, Kajen District. The study focuses on planning, implementation, reporting, and accountability aspects of BOP management. A qualitative approach with a case study design was employed. Data were collected through interviews, observations, and documentation, while data validity was ensured through credibility, transferability, dependability, and confirmability techniques. The results indicate that BOP management at TK Negeri Pembina has applied management principles involving the principal, treasurer, teachers, and school committee. Planning is conducted through the preparation of the School Activity and Budget Plan (RKAS) using the ARKAS application to enhance financial efficiency. Implementation follows the approved RKAS, while recording and reporting are carried out systematically and transparently. Accountability reflects effectiveness, efficiency, and flexibility, supported by supervision from the principal, school committee, and the Education Office. However, challenges include delays in fund disbursement and limited transparency to parents. Overall, BOP utilization contributes to improving educational quality through enhanced teacher competence, provision of learning media, and strengthened school-based management.